Construction of Laser Raman System Using Diode Laser and Its Performance - Abedin, Kazi M; Habib, M Ahasan; Wahadoszamen, M; Talukder, Aminul I; Haider, AFM Yusuf (Journal of Bangladesh Academy of Sciences, 2009)
We constructed a laser Raman system using a commercially available infrared diode laser. The diode laser is used without any temperature controller in a stabilized power supply. Good quality Raman spectra of sufficient wavelength resolution were obtained for a variety of chemicals and products, including solid samples. Raman spectra of several edible oils and ghee were also obtained and these were found to be largely free of fluorescence. Finally, Raman spectra of an artificial sweetener and a pharmaceutical product were obtained, showing the feasibility and reliability of the present Raman system in real-life situation. DOI: 10.3329/jbas.v33i1.2950 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 55-62, 2009